A carbosilane dendrimer bonded silica as the stationary phase for capillary electrochromatography. Issue 16 (21st August 2015) - Bao, James J.; Sun, Chaohui; Li, Youxin; Yuan, Ruijuan; Xu, Hui; chen, Guowen; Feng, Shengyu
<x xml:space="preserve">Abstract</x> A novel carbosilane dendrimer bonded silica (G2-silica) was synthesized and evaluated as a potential chromatographic resin.